2015
DOI: 10.4172/2161-0495.1000248
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy Outcomes with Paternal Exposure to Finasteride, a Synthetic 5-Alpha-Reductase Inhibitor: A Case Series

Abstract: Finasteride (a synthetic 5-alpha-reductase inhibitor) is used for the treatment of male pattern baldness and benign prostatic hyperplasia. There have been few reports on pregnancy outcomes after paternal exposure to finasteride either prior to or during pregnancy. Nineteen cases with documented paternal exposure to finasteride either prior to or during pregnancy were identified through the Korean Motherisk program. Detailed patient histories were obtained and each patient was followed from pregnancy through ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 8 publications
0
1
0
Order By: Relevance
“…52,53 Despite animal studies suggesting that finasteride teratogenicity after paternal exposure is unlikely due to the low concentration of finasteride absorbed in semen, there have been some reported cases of teratogenicity after paternal exposure and a possible association with spontaneous abortion. [54][55][56][57] For these reasons, it has been recommended by some researchers that males taking finasteride should avoid unprotected intercourse with a female partner who is or may be pregnant and discontinue finasteride before conceiving. 33,46,58 No mechanism has been elucidated for a finasteride-induced spontaneous abortion, although inadequate secretion of progesterone, uterine cervix stenosis, and sperm chromosomal abnormalities have been suggested as possible mechanisms.…”
Section: Finasteride Teratogenicitymentioning
confidence: 99%
See 1 more Smart Citation
“…52,53 Despite animal studies suggesting that finasteride teratogenicity after paternal exposure is unlikely due to the low concentration of finasteride absorbed in semen, there have been some reported cases of teratogenicity after paternal exposure and a possible association with spontaneous abortion. [54][55][56][57] For these reasons, it has been recommended by some researchers that males taking finasteride should avoid unprotected intercourse with a female partner who is or may be pregnant and discontinue finasteride before conceiving. 33,46,58 No mechanism has been elucidated for a finasteride-induced spontaneous abortion, although inadequate secretion of progesterone, uterine cervix stenosis, and sperm chromosomal abnormalities have been suggested as possible mechanisms.…”
Section: Finasteride Teratogenicitymentioning
confidence: 99%
“…33,46,58 No mechanism has been elucidated for a finasteride-induced spontaneous abortion, although inadequate secretion of progesterone, uterine cervix stenosis, and sperm chromosomal abnormalities have been suggested as possible mechanisms. 56,57…”
Section: Finasteride Teratogenicitymentioning
confidence: 99%
“…Initially, it was suggested that there was still no documented full-term pregnancy or live birth from couples in which the man had received finasteride [15], so caution has been advised regarding the use of finasteride by male members of couples who are planning to have children [22]. Probably for these reasons, in 2015 in South Korea, a clinical study was conducted which proved that in 19 couples with documented paternal exposure to finasteride, 13 couples (68.4%) gave birth to normal full-term babies, and six cases (31.6%) resulted in spontaneous (n = 3) or artificial (n = 3) abortions [23]. In our previous study [24], we observed a low number of pups in the litters of female rats fertilized by finasteride-treated male rats.…”
Section: Introductionmentioning
confidence: 99%